Paper girls. 5 - Vaughan, Brian K. (Image Comics, 2018)
"Can anyone escape fate? That's what Mac and her fellow newspaper delivery girls must discover as they travel from the year 2000 to a distant and dangerous future edition of Cleveland, Ohio."--Back cover.